The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/nag.499
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of the behaviour of a heat exchanger pile

Abstract: SUMMARYThe geothermal use of concrete geostructures (piles, walls and slabs) is an environmentally friendly way of cooling and heating buildings. With such geothermal structures, it is possible to transfer energy from the ground to fluid-filled pipes cast in concrete and then to building environments. To improve the knowledge in the field of geothermal structures, the behaviour of a pile subjected to thermo-mechanical loads is studied in situ. The aim is to study the increased loads on pile due to thermal effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
251
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(266 citation statements)
references
References 5 publications
13
251
0
2
Order By: Relevance
“…Codes developed for use with borehole heat exchangers, eg [15,16] are equally applicable to pile applications. In addition, numerical methods may be used to couple the thermal and mechanical aspects of the pile behaviour [17]. This paper makes used of numerical solution of the diffusion equation to consider a wide range of pile heat exchanger geometries.…”
Section: Existing Design Approachesmentioning
confidence: 99%
“…Codes developed for use with borehole heat exchangers, eg [15,16] are equally applicable to pile applications. In addition, numerical methods may be used to couple the thermal and mechanical aspects of the pile behaviour [17]. This paper makes used of numerical solution of the diffusion equation to consider a wide range of pile heat exchanger geometries.…”
Section: Existing Design Approachesmentioning
confidence: 99%
“…The extent to which this heating zone extends continues to grow up to t ¼ 120 min, at which point no further changes were detected. these observed changes in soil temperature along the length of an energy pile that have been postulated by Laloui et al (2006), Bourne-Webb et al (2009), andBrandl (2006) as the likely contributing factor for increased foundation movements in geothermal structures due to changes in side friction characteristics arising from thermal expansion and contraction of the soil.…”
Section: Energy Pile Applicationmentioning
confidence: 66%
“…Only three studies have been identified: one in Austria (Brandl, 1998), one in Switzerland (Laloui et al, 2006) and one in the UK (Bourne-Webb et al, 2009). The authors are aware of some other tests carried out in Australia and the US, but the results of these tests have not been published yet.…”
Section: Geostructural Behaviour Of Energy Pilesmentioning
confidence: 99%
“…The three published cases, while providing useful insights into the behaviour of these systems, have shortcomings, such as presenting incomplete information and not being representative of an operational system or being of short duration (Bourne-Webb et al, 2012). The results of these in situ experiences show that application of a thermal load induces a significant change in the structural behaviour of a foundation pile (Amis et al, 2008;Bourne-Webb et al, 2009;Laloui et al, 2006). In general, the previous studies showed that heating of a pile induces an additional compression stress in the pile and increases the mobilised shear stress.…”
Section: Geostructural Behaviour Of Energy Pilesmentioning
confidence: 99%